System of Monitoring and Evaluation - Misra, Smita (Washington, DC, 2014)
Monitoring and evaluation (M&E) are important performance management tools. They help in ascertaining whether the policies and programs are meeting the objectives. They can provide useful feedback information for taking corrective actions in the design of policies and programs. They are also the basis for accountability in the use of program funds. The monitoring and evaluation of the rural water supply programs in India is being done mainly through periodic physical and financial progress reports, visits of area officers and other government officials, and evaluation studies and sample surveys conducted from time to time. The main purpose of the monitoring and evaluation activities is to find out whether programs are being implemented as per their objectives, and to identify bottlenecks, if any, in the implementation of the programs.